Microglial Phagocytosis/Cell Health High‐Content Assay. Issue 3 (27th March 2023) - Mason, Emily R.; Soni, Disha M.; Chu, Shaoyou
Abstract: We report a microglial phagocytosis/cell health high‐content assay that has been used to test small molecule chemical probes and support our drug discovery projects targeting microglia for Alzheimer's disease therapy. The assay measures phagocytosis and cell health (cell count and nuclear intensity) simultaneously in 384‐well plates processed with an automatic liquid handler. The mix‐and‐read live cell imaging assay is highly reproducible with capacity to meet drug discovery research needs. Assay procedures take 4 days including plating cells, treating cells, adding pHrodo‐myelin/membrane debris to cells for phagocytosis, staining cell nuclei before performing high‐content imaging, and analysis. Three selected parameters are measured from cells: 1) mean total fluorescence intensity per cell of pHrodo‐myelin/membrane debris in phagocytosis vesicles to quantify phagocytosis; 2) cell counts per well (measuring compound effects on proliferation and cell death); and 3) average nuclear intensity (measuring compound induced apoptosis). The assay has been used on HMC3 cells (an immortalized human microglial cell line), BV2 cells (an immortalized mouse microglial cell line), and primary microglia isolated from mouse brains. Simultaneous measurements of phagocytosis and cell health allow for the distinction of compound effects on regulation of phagocytosis from cellular stress/toxicity related changes, a distinguishing feature of the assay. The combination of cell counts and nuclear intensity as indicators of cell health is also an effective way to measure cell stress and compound cytotoxicity, which may have broad applications as simultaneous profiling measurements for other phenotypic assays. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. This article was corrected on 06 April 2023. See the end of the full text for details. Basic Protocol : Microglial phagocytosis/cell health high‐content assay protocol Support Protocol : Procedures to isolate myelin/membrane debris from mouse brain and label with pHrodo